Changes of Money Supply, Interest Rates, Foreign Exchange and Economic Growth in the Euro Area - Bukowski, Sławomir Ireneusz; Bukowska, Joanna Emilia (Acta Universitatis Lodziensis. Folia Oeconomica, 2018)
The aim of the research, which results are presented in this paper was answer the question: what was the impact of changes in aggregate M3, interest rates, foreign exchange EUR/USD on the economic growth in the euro area in the period of 2008–2016. The econometric model VAR was applied in research. The Analysis of the model’s estimation results indicates that effectiveness of economic growth stimulation by quantitative easing and interest rate policy in the euro area was relatively very weak.